AVG delamination: a cause of early cannulation arteriovenous graft dysfunction in hemodialysis patients - Wang, Yufei; Liu, Yamin; Liang, Xianhui; Wang, Pei (Annals of medicine (Helsinki), 2024)
A series of cases have reported graft delamination as a rare complication of early-cannulation arteriovenous graft (ecAVG). The unique multilayer structure of ecAVGs contributes to the property of cannulation as early as hours after implantation, but on other hand it takes the risk of graft delamination. However, the underlying mechanism and management of graft delamination as well as its effects on the long-term patency of ecAVGs have not been systemically analyzed. A retrospective study was conducted in a cohort of patients who required an ecAVG for hemodialysis (HD) access in our center between April 2017 and December 2021. The characteristics of graft delamination and the outcomes of its different treatments were analyzed. A total of 144 ecAVGs were established in 141 end-stage renal disease (ESRD) patients, including 124 (86.1%) Acuseal grafts and 20 (13.9%) Flixene grafts. During follow-up 24.5(11.5, 45.8) months, 11 (7.6%) subjects had graft infection with an incidence of 0.03 patient-year. Thirteen (9.0%) subjects had graft delamination at 9.3(5.0,12.4) months after ecAVG implantation, with an incidence of 0.04 per patient-year. ecAVG delamination was observed in both Acuseal grafts (0.037 per patient-year) and Flixene grafts (0.055 per patient-year). Thrombosis or venous hypertension was the most common complaints. Seven delamination was observed at 1.3 (0.1, 4.2) months after an endovascular procedure. The primary patency, primary assistant patency and secondary patency in delamination group were significantly lower than that in non-delamination group ( < 0.05). Post-procedure primary patency of group A (percutaneous transluminal angioplasty, PTA), group B (stenting) and group C (partial graft replacement, PGR) were 1.3 (0.45,4.22) months, 5.3 (3.05,6.85) months and 8.45 (4.78,14.53) months respectively ( = 0.029). Graft delamination was not a rare complication of ecAVGs in this cohort. It significantly reduced the long-term patency of AVGs. PGR might be a more effective therapeutic way than endovascular treatments.